GLOBAL SOFTWARE DEVELOPMENT: A HARD PROBLEM REQUIRING A HOST OF SOLUTIONS. - SIMONS, MATTHEW (Communications of the ACM, 2006)
The article focuses on Globally Distributed Software Development (GSD). The author discusses how he has developed software, while based in India, with work teams in India, the United States and United Kingdom. The author discusses how he uses story cards to manage his projects. The article discusses how agile development processes can be applied to software being developed by GSD. Among the practices the author discusses are: test-driven development, continuous integration, pair programming and other processes.